Mammographic Screening in Older Women: When Is It Time to Stop?. Issue 2 (14th March 2020) - Butler, Reni; Philpotts, Liane
Abstract: Mammographic screening guidelines in women aged 75 and older are inconsistent due to a lack of data from prospective randomized controlled trials, such as those that exist for women between 40–74 years of age. In addition, older women are perceived as less likely to benefit from early detection due to increased comorbidities and a greater proportion of biologically favorable cancers. With increasing life expectancy and quality of life in the elderly, the question of when to stop mammographic screening merits renewed discussion. Observational data support a survival benefit from regular screening in older women with no severe comorbidities. In addition, screening mammography in this age group has been shown to perform better than in younger age groups, tipping the balance toward greater benefits than harms. Early studies of digital breast tomosynthesis (DBT) in older women suggest that performance metrics are further improved with DBT screening. While a biennial schedule in older women preserves some of the benefit of screening, annual mammography achieves the greatest reductions in breast cancer mortality and morbidity. As the medical community strives to offer personalized care for all age groups, health care providers are well positioned to offer shared decision-making based on existing data and tailored to each woman's individual risk profile, comorbid conditions, and personal values.